The effect of organization culture and internal control on corporate governance and its impact on state owned enterprises performance in Indonesia - Maya Sari (Proceedings of AICS - Social Sciences, 2017)
This study measured four variables, namely, organizational culture, and internal control as exogenous variables as well as corporate governance and corporate performance as an endogenous variable. To collect data using survey techniques on state-owned companies in Indonesia. The population of this research is State-owned companies in Indonesia 119 SOEs either state-owned, opened state-owned, and Housing (perum). The samples of this research are 105 companies. The respondent of this research is all company managers of SOEs in Indonesia's state-owned enterprises and state-owned company in Indonesia. The data were analyzed using Structural Equation Modelling with LISREL application. The results showed that there is significant influence of organizational culture on corporate governance, internal control of corporate governance, organizational culture on corporate performance, corporate governance influence on corporate performance. From the test direct effect has no significant effect of internal control to corporate performance. Corporate governance is an intervening variable relation between the internal control and corporate performance.